2023
DOI: 10.1101/2023.02.09.527935
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Potent and Selective CDKL5/GSK3 Chemical Probe is Neuroprotective

Abstract: Despite mediating several essential processes in the brain, including during development, cyclin-dependent kinase-like 5 (CDKL5) remains a poorly characterized human protein kinase. Accordingly, its substrates, functions, and regulatory mechanisms have not been fully described. We realized that availability of a potent and selective small molecule probe targeting CDKL5 could enable illumination of its roles in normal development as well as in diseases where it has become aberrant due to mutation. We prepared a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…CDKL5, also known as serine/threonine kinase 9 (STK9), is the only member of the CDKL family with strong connections to ciliogenesis in humans. CDKL5 is ubiquitously expressed in human tissues, but is observed at higher levels in the hippocampus, cerebellar, striatum, and cortex regions of the CNS in humans and mice, consistent with its roles in dendritic spine growth, brain development, and excitatory synapse composition (Rusconi et al, 2008;Fagerberg et al, 2014;Canning et al, 2018;Ong et al, 2023). A study using RNAi targeting CDKL5, which caused reduced neurite growth and dendritic arborization in rat cortical neurons, confirmed that this kinase regulates neuronal morphogenesis (Chen et al, 2010).…”
Section: Cdkl Familymentioning
confidence: 71%
See 2 more Smart Citations
“…CDKL5, also known as serine/threonine kinase 9 (STK9), is the only member of the CDKL family with strong connections to ciliogenesis in humans. CDKL5 is ubiquitously expressed in human tissues, but is observed at higher levels in the hippocampus, cerebellar, striatum, and cortex regions of the CNS in humans and mice, consistent with its roles in dendritic spine growth, brain development, and excitatory synapse composition (Rusconi et al, 2008;Fagerberg et al, 2014;Canning et al, 2018;Ong et al, 2023). A study using RNAi targeting CDKL5, which caused reduced neurite growth and dendritic arborization in rat cortical neurons, confirmed that this kinase regulates neuronal morphogenesis (Chen et al, 2010).…”
Section: Cdkl Familymentioning
confidence: 71%
“…CDKL kinases are a family of five relatively underexplored serine/threonine human kinases: CDKL1, CDKL2, CDKL3, CDKL4, and CDKL5. This family has the highest sequence similarity to cyclin-dependent kinases (CDKs) (Canning et al, 2018;Ong et al, 2023). CDKLs contain a cyclin binding domain, although no cyclin-dependent functions have been ascribed.…”
Section: Cdkl Familymentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the CDKL5 gene exhibits overexpression with an over-accessible promoter region (protein levels are unavailable). Suppressing CDKL5 expression using a small molecule probe enhances the survival of human motor neurons under endoplasmic reticulum stress conditions 50 . Another outlier gene we identified, HIF1A, contributes to motor neuron degeneration through hypoxic stress, and prolonged survival observed in ALS mice suggests up-regulation of HIF1A as a potential therapeutic target 51 .…”
Section: Analyzing Outliers Across Multiple Omics Levels Reveals Pote...mentioning
confidence: 99%
“…We manually curated a list of ALS genes from literature 1,11,[42][43][44][45][46][47][49][50][51][73][74][75][76][77][78][79][80][81][82] and ALSOD 41 . The curated list is available at 10.5281/zenodo.8331545.…”
Section: Curation Of Genes Associated With Neurodegenerative Diseasesmentioning
confidence: 99%